ANALISIS PELAPORAN SPT MASA PPN DAN SPT PPH BADAN DALAM PENYUSUNAN LAPORAN KEUANGAN PADA PT.MITRA JAYA KENCANA INDAH MEDAN - Wesly Simanjuntak (JURNAL ILMIAH KOHESI, 2018)
This study aims to determine the amounts listed on the tax invoice, whether obtained from the purchase transaction or from sales transactions reported in the VAT Notification Period (SPT Masa PPN). The purpose of this research is to increase knowledge about equalization mechanism between SPT Per VAT period and SPT Annual Body and impact of the mechanism tersbeut against SPT Annual AgencyThe conclusion of this research is that the company has done equalization between SPT Masa PPN with SPT PPh Agency at the time will report the Income Tax Body. The cause of the difference due to the delivery of non-voting VAT and does not make the tax invoice so that the value of business in the SPT Annual Income Tax Agency becomes greater than business circulation on the VAT tax returns.Suggestions that can be given is for the company to rectify SPT VAT Period so that the business peredaraan value listed in SPT VAT Period Become the same as the value listed in the Annual Income Tax Return